2021
DOI: 10.47102/annals-acadmedsg.2020505
|View full text |Cite
|
Sign up to set email alerts
|

Association of APOE polymorphisms with lipid-lowering efficacy of statins in atherosclerotic cardiovascular diseases

Abstract: Introduction: Apolipoprotein E (APOE) gene is a promising candidate for the diagnosis of hyperlipoproteinaemia and atherosclerosis. Polymorphisms in APOE have been reported to result in differential efficacies of statins in atherosclerotic cardiovascular diseases. Method: We classified APOE genotypes of 225 patients treated with atorvastatin and analysed the relationship between genotypes and blood lipid levels. Results: The baseline levels of total cholesterol (TC) and low-density lipoprotein cholesterol (LDL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Polymorphisms of genes that involve in the regulation of lipid metabolisms such as apolipoprotein E (apo E), cholesteryl ester transfer protein (CETP), and liver X receptors (LXR) have been reported to correlate with the efficacy of statin and susceptibility to cardiovascular disease. [6][7][8][9][10][11] Several studies have revealed that the genetic variants of the pharmacokinetics-related genes result in the diversity of statin efficacy among individuals. [12][13][14] Since statins have the primary site of action and metabolism in the liver, where they inhibit HMG-CoA reductase, the genetic variations of Phase I and II drug-metabolizing enzymes and drug transporter genes may have a critical role in the concentration of statins within hepatocytes and plasma, and consequently clinical efficacy to the treatment of statin.…”
Section: Introductionmentioning
confidence: 99%
“…Polymorphisms of genes that involve in the regulation of lipid metabolisms such as apolipoprotein E (apo E), cholesteryl ester transfer protein (CETP), and liver X receptors (LXR) have been reported to correlate with the efficacy of statin and susceptibility to cardiovascular disease. [6][7][8][9][10][11] Several studies have revealed that the genetic variants of the pharmacokinetics-related genes result in the diversity of statin efficacy among individuals. [12][13][14] Since statins have the primary site of action and metabolism in the liver, where they inhibit HMG-CoA reductase, the genetic variations of Phase I and II drug-metabolizing enzymes and drug transporter genes may have a critical role in the concentration of statins within hepatocytes and plasma, and consequently clinical efficacy to the treatment of statin.…”
Section: Introductionmentioning
confidence: 99%